Detroit and the "Good War" : the World War II letters of Mayor Edward Jeffries and friends - Jeffries, Edward, 1900-1950 (University Press of Kentucky, 1996)
Edward J. Jeffries Jr., was elected mayor of Detroit in 1937 and for a decade led the city through a period of race riots, union turmoil, and unprecedented growth. Jeffries's circle of friends was made up primarily of newspaper reporters who shared his interests and lifestyle. Devoted to family, they nevertheless worked long hours, smoked heavily, drank moderately, and gambled often in their running card games of gin and poker. After Pearl Harbor, Jeffries watched his closest friends, most twelve to fourteen years his junior, enlist in the armed forces. Voracious letter writers, over the next f.